High-stability easily-pumped light-weight high-strength concrete and preparation method thereof
Through the pressure grouting treatment and density adjustment of modified fly ash ceramic granules and shale ceramic sand, combined with the amount of drift beads, the stability and brittleness of lightweight high-strength concrete are solved, and the stable application of lightweight high-strength concrete in the main structure is achieved.
Patent Information
- Application Number
- CN202510561129.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2025-07-18
AI Technical Summary
Lightweight high-strength concrete has poor fluidity and stability, the aggregate is prone to float, has high brittleness, poor anti-seepage performance, and has large early shrinkage, resulting in limited application range, especially in the main structure, which can easily cause transmission pipe blockage and engineering quality problems.
Grouting modified fly ash ceratops and saturated dry shale clay sand are used to adjust the density of light aggregates through pressure grouting treatment and drainage method volume measurement, combined with the amount of drift beads to ensure the stability of light aggregates in concrete, and use staged mixing technology to prepare high-stability and easy-to-pump lightweight high-strength concrete.
It improves the stability and strength of lightweight high-strength concrete, reduces the floating phenomenon of light aggregates, enhances the anti-seepage performance, ensures the overall stability and safety of concrete, and is suitable for the application of main structures.
Smart Images

Figure CN120328941A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of concrete, and particularly relates to a highly stable, easily pumpable lightweight high-strength concrete and a preparation method thereof. Background Art
[0002] At present, urban renewal and the green and sustainable development of the construction industry have become important growth points for the development of the construction industry. The main cementitious material of traditional bulk building material concrete, cement, has a high carbon emission, and the exploitation of natural sand and gravel is prone to cause ecological environment damage. How to reduce the consumption of traditional concrete in high-rise buildings or long-span structures and develop new low-carbon structural materials has become a difficult problem to be solved urgently. The main way to solve this difficult problem is to develop lightweight high-strength concrete. The application of lightweight high-strength concrete can further reduce the structural self-weight, reduce the member cross-section, and decrease the structural self-weight. The lightweight high-strength concrete prepared with lightweight aggregates has the above advantages, and artificial lightweight aggregates are usually prepared from industrial solid waste powder through processes such as pulping, granulation, and drying, which can effectively absorb industrial solid waste and realize the reuse of waste.
[0003] However, the density of lightweight aggregates is relatively low and the brittleness is relatively high, mainly due to their porous structure. The porosity of shale ceramsite can reach more than 50%. The multiple pore structures in lightweight aggregate concrete will seriously affect the durability and mechanical properties of concrete. Therefore, the performance of lightweight high-strength concrete prepared with lightweight aggregates is quite different from that of ordinary concrete. Although lightweight high-strength concrete has both lightweight and high-strength properties, there are still the following technical problems: lightweight high-strength concrete usually has poor fluidity and stability, and the aggregates are easy to float; its brittleness is relatively high and it is easy to crack; its impermeability is poor and the early shrinkage is large. These problems severely limit its application range, and its main application occasions are thermal insulation structures and enclosure structures, and it is rarely used in main structures. Among these technical problems, the floating of lightweight aggregates is the main reason for the instability of lightweight concrete, which is extremely likely to cause problems such as blockage of conveying pipes, delamination and honeycombing of hardened concrete structures, and engineering quality and safety problems.
[0004] Therefore, how to provide a highly stable, easily pumpable lightweight high-strength concrete and a preparation method thereof is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the Invention
[0005] Aiming at the problems that the floating of lightweight aggregates leads to the instability of lightweight concrete, which is extremely likely to cause problems such as blockage of conveying pipes, delamination and honeycombing of hardened concrete structures, and engineering quality and safety problems, the present invention proposes a highly stable, easily pumpable lightweight high-strength concrete and a preparation method thereof, to solve the problems of floating of lightweight aggregates and high brittleness in lightweight high-strength concrete, and to achieve the goal of large-scale application of lightweight high-strength concrete.
[0006] To solve the above technical problems, the present invention includes the following technical solutions: A highly stable, lightweight, high-strength concrete, wherein the weight ratio of each component of the concrete is (kg / m 3 ): Grouting modified fly ash ceramsite 730~870, saturated surface dry shale ceramsite sand 300~500, cement 450~550, silica fume 40~60, ordinary sand 260~290, water reducer 5~7, floating beads 0~100 and water 50~80.
[0007] A method for preparing highly stable lightweight high-strength concrete comprises the following steps: Step S1, pretreatment: pre-wetting the fly ash ceramsite and shale ceramsite sand respectively to a saturated surface dry state, and at the same time, mixing water and a water reducing agent to form a chemical admixture solution; Step S2, grouting modification: using a grouting pump to perform pressure grouting treatment on the saturated surface dry fly ash ceramsite to obtain a mixed slurry, wherein the grouting liquid ratio used in the pressure grouting is: by mass, 450-550 parts of cement, 40-60 parts of silica fume, 5-7 parts of water reducer, and 100-160 parts of water; Step S3, density determination: The volume of the ceramsite modified by grouting is measured by drainage method, and the formula ; Calculate the density of modified ceramsite ρ T , where m0 is the mass of fly ash ceramsite, V is the volume of the capacity cylinder, V 排 The volume of clean water discharged; the volume measurement of drainage method includes: placing the fly ash ceramsite modified by pressure grouting in a ventilated and dry place to dry, and pouring it into the concrete volume cylinder after the surface is completely hardened. The fly ash ceramsite can be added to the top of the concrete volume cylinder to ensure the maximum measurement sample mass. Pour out the ceramsite, weigh its mass m0, and then pour the ceramsite back into the volume cylinder. Inject clean water into the concrete volume cylinder to the top of the volume cylinder, take out the fly ash ceramsite and pour out the clean water, and use a measuring cup or other weighing instrument to measure the volume of clean water discharged. Calculate the density of fly ash ceramsite modified by pressure grouting according to the above formula.
[0008] Step S4: Density balance adjustment: According to the formula ; Calculate the density of the mortar by adding 0~100kg of floating beads to make ρ B =ρ T ; Step S5, mixing in stages: in the first stage, silica fume, cement, buoyant beads and ordinary sand are dry mixed for 2.0-3.0 minutes; in the second stage, shale ceramic sand and chemical admixture solution are added and mixed for 3-4 minutes; in the third stage, modified ceramsite is added and mixed for 3.0-5.0 minutes to obtain high-stability, lightweight and high-strength concrete.
[0009] Furthermore, in the volume measurement by the drainage method, a 10L standard test cylinder is selected for the volume of the measuring cylinder, and the filling height error is controlled within ±5mm during measurement.
[0010] Furthermore, the amount of cenospheres added is calculated by the linear fitting formula ; where a is the slope, b is the intercept; x is the mass of the added cenospheres, in kg; ρ B is the density of the mortar, in kg / m 3 .
[0011] Furthermore, the following proportions are adopted for each component: 800kg of fly ash ceramsite, 400kg of shale ceramsand, 500kg of cement, 50kg of silica fume, 275kg of ordinary sand, 6kg of water reducer, 65kg of water; the proportion of the grouting liquid is 500kg of cement, 50kg of silica fume, 6kg of water reducer, 125kg of water; Density of saturated surface dry shale ceramsand: 1208 kg / m³; Density of cement: 3100 kg / m³; Density of silica fume: 900 kg / m³; Density of ordinary sand: 2600 kg / m³; Density of water reducer: 1100 kg / m³; Density of water: 1000 kg / m³; Density of cenospheres: 500kg / m³; The linear equation obtained by fitting is ρ B =-2.7788x + 1778.8 Since ρ B =ρ T , so substitute ρ T into the linear equation to calculate the appropriate amount of cenospheres added.
[0012] Compared with the prior art, the present invention has the following advantages and beneficial effects: The present invention provides a high-stability, easy-to-pump lightweight high-strength concrete and its preparation method. The mass ratio of each component of the concrete is (kg / m 3): 730 - 870 of grouting - modified fly - ash ceramsite, 300 - 500 of saturated surface - dry shale ceramsite sand, 450 - 550 of cement, 40 - 60 of silica fume, 260 - 290 of ordinary sand, 5 - 7 of water - reducing agent, 0 - 100 of cenospheres and 50 - 80 of water. The preparation method of the lightweight high - strength concrete includes: 1. Pretreatment: Pre - wet the fly - ash ceramsite and shale ceramsite sand respectively to the saturated surface - dry state, and at the same time mix water and water - reducing agent to form a chemical admixture solution; 2. Grouting modification: Use a grouting pump to conduct pressure grouting treatment on the saturated surface - dry fly - ash ceramsite; 3. Density measurement: Measure the volume of the grouting - modified ceramsite by the drainage method and calculate the density of the modified ceramsite; 4. Density balance adjustment: Analyze the relationship between the mortar density and the cenosphere dosage, calculate the cenosphere dosage, and make the density of the mortar equal to the density of the pressure - grouting - modified fly - ash ceramsite by adding 0 - 100 kg of cenospheres; 5. Stir in three stages to prepare a lightweight high - strength concrete with high stability.
[0013] Compared with the prior art, the beneficial effects of the present invention are mainly as follows: (1) For the lightweight high - strength concrete with high stability provided by the present invention, when the density of the shale ceramsite mortar after adjustment is close to that of the pressure - grouting - modified fly - ash ceramsite, the lightweight aggregates are not easy to float or sink in the concrete. Although the small amount of air bubbles contained in the concrete and the minor material losses during batching due to operation cause a deviation between the actual density and the calculated density of the mortar liquid, when the lightweight aggregates move, they will be affected by the frictional resistance and return to the equilibrium position again. Similarly, when there are minor density changes in the main materials such as the cementitious materials and shale ceramsite sand in the mortar due to different batches, during the floating or sinking movement of the lightweight aggregates, they will also be affected by the frictional resistance, and the lightweight aggregates will return to the equilibrium position again, thus ensuring the stability of the concrete.
[0014] (2) For the lightweight high - strength concrete with high stability provided by the present invention, after the inorganic lightweight aggregates are treated by pressure grouting, the water in the open or connected pores on the surface and near the surface is replaced by the cementitious material slurry, reducing the structural defects in the interfacial transition zone between the lightweight aggregates and the mortar in the concrete; after the filled lightweight aggregate shell hardens, its strength is higher, which can effectively resist the load, relieve the brittle cracking trend of the lightweight aggregates, and improve the strength of the concrete. In addition, since the cementitious material slurry still contains fine particles, it is difficult to penetrate into the near - center part of the lightweight aggregates. Therefore, the lightweight aggregates treated by pressure grouting still have the lightweight characteristics, that is, the concrete still has the lightweight characteristics. Brief Description of the Drawings
[0015] Figure 1 It is a schematic diagram of the pressure grouting treatment in the preparation method of the lightweight high - strength concrete with high stability in an embodiment of the present invention; Figure 2Schematic diagram of density measurement of fly ash ceramsite after pressure grouting modification in the preparation method of high-stability lightweight high-strength concrete in an embodiment of the present invention; Figure 3 Schematic diagram of the calculated linear fitting relationship of cenospheres in the preparation method of high-stability lightweight high-strength concrete in an embodiment of the present invention; Figure 4 Image of the concrete failure surface of test group 1 in the preparation method of high-stability lightweight high-strength concrete in an embodiment of the present invention; Figure 5 Image of the concrete failure surface of test group 2 in the preparation method of high-stability lightweight high-strength concrete in an embodiment of the present invention. Detailed implementation manners
[0016] The following further details a high-stability easy-pumping lightweight high-strength concrete and its preparation method provided by the present invention in conjunction with the accompanying drawings and specific embodiments. According to the following description, the advantages and features of the present invention will be clearer.
[0017] Embodiment 1
[0018] The following combines Figures 1 to 5 , and details the high-stability easy-pumping lightweight high-strength concrete and its preparation method of the present invention.
[0019] A high-stability lightweight high-strength concrete, and the components of the concrete are in a mass ratio of (kg / m 3 ): 730 - 870 parts of grouted modified fly ash ceramsite, 300 - 500 parts of saturated surface dry shale ceramsite sand, 450 - 550 parts of cement, 40 - 60 parts of silica fume, 260 - 290 parts of ordinary sand, 5 - 7 parts of water reducer, 0 - 100 parts of cenospheres, and 50 - 80 parts of water.
[0020] The preparation method of the high-stability lightweight high-strength concrete includes the following steps: Step S1, pretreatment: pre-wet the fly ash ceramsite and shale ceramsite respectively to the saturated surface dry state, and at the same time mix water and water reducer to form a chemical admixture solution; Step S2, grouting modification: use a grouting pump to perform pressure grouting treatment on the saturated surface dry fly ash ceramsite to obtain a mixed slurry. Among them, the mixing ratio of the grouting liquid used for the pressure grouting is: by mass, 450 - 550 parts of cement, 40 - 60 parts of silica fume, 5 - 7 parts of water reducer, and 100 - 160 parts of water.
[0021] Step S3, density measurement: measure the volume of the grouted modified ceramsite by the drainage method, and through the formula ; calculate the density of the modified ceramsite, where m0 is the mass of fly ash ceramsite,V is the volume of the capacity cylinder, V 排 is the volume of the discharged clean water; specifically, place the pressure-grouted and modified fly ash ceramsite in a ventilated and dry place to dry. After the surface is completely hardened, pour it into the concrete capacity cylinder. The fly ash ceramsite can be added to the top of the concrete capacity cylinder to ensure the maximum mass of the measurement sample. Pour out the ceramsite and weigh its mass m0, and then pour the ceramsite back into the capacity cylinder. Inject clean water into the concrete capacity cylinder to the top, and then pour out the clean water. Use a measuring cup or other weighing instrument to measure the volume V of the discharged clean water 排 .
[0022] Step S4, density balance adjustment: ; Further simplification yields the following formula: ; Since ; and ; are both constant terms. Let ; ; Then the above formula can be further transformed into: ; —— The dosage of saturated surface-dry shale ceramsite per cubic meter of concrete (kg); —— The dosage of cement per cubic meter of concrete (kg); —— The dosage of silica fume per cubic meter of concrete (kg); —— The dosage of ordinary sand per cubic meter of concrete (kg); —— The dosage of water reducer per cubic meter of concrete (kg); —— The dosage of water per cubic meter of concrete (kg); —— The dosage of cenospheres per cubic meter of concrete (kg); —— The density of saturated surface-dry shale ceramsite (kg / m3); —— The density of cement (kg / m3); —— The density of silica fume (kg / m3); —— The density of ordinary sand (kg / m3); ——Density of water reducing agent (kg / m³); ——Density of water (kg / m³); ——Density of cenospheres (kg / m³); Calculate the density of mortar according to the foregoing formula. By adding 0 - 100 kg of cenospheres, make ρ B =ρ T , so that the fly ash ceramsite is in mechanical equilibrium in the mortar and does not float or sink. The cenospheres are lightweight cenospheres with a density range of 400 - 750 kg / m 3 .
[0023] Step S5: Stir in stages: In the first stage, dry - mix silica fume, cement, cenospheres, and ordinary sand for 2.0 - 3.0 min; in the second stage, add shale ceramsite and chemical admixture solution and mix for 3 - 4 min; in the third stage, add modified ceramsite and mix for 3.0 - 5.0 min to obtain high - stability lightweight high - strength concrete.
[0024] In this embodiment, more preferably, in the volume measurement by the drainage method, a 10 L standard test cylinder is selected for the volume of the measuring cylinder, and the filling height error is controlled within ±5 mm during measurement.
[0025] In this embodiment, more preferably, the dosage of cenospheres is calculated by the linear fitting formula ;
[0026] where a is the slope, b is the intercept, x is the mass of added cenospheres in kg; ρ B is the density of mortar in kg / m 3 .
[0027] In this embodiment, more preferably, the following ratios are used for each component: 800 kg of fly ash ceramsite, 400 kg of shale ceramsite, 500 kg of cement, 50 kg of silica fume, 275 kg of ordinary sand, 6 kg of water - reducing agent, 65 kg of water; the ratio of grouting liquid is 500 kg of cement, 50 kg of silica fume, 6 kg of water - reducing agent, 125 kg of water. Saturated surface - dry shale ceramsite density: 1208 kg / m³; cement density: 3100 kg / m³; silica fume density: 900 kg / m³; ordinary sand density: 2600 kg / m³; water - reducing agent density: 1100 kg / m³; water density: 1000 kg / m³; cenospheres density: 500 kg / m³; The linear equation obtained by fitting is ρ B =-2.7788x + 1778.8 Since ρ B =ρ T , therefore, substitute ρT Substitute into the linear equation to calculate the appropriate content of cenospheres.
[0028] The following is a detailed description in combination with the mix proportion tables and performance test results of Experimental Group 1 and Experimental Group 2: Table 1 is the mix proportion table of high-stability lightweight high-strength concrete.
[0029] Table 1 Mix Proportion Table of High-Stability Lightweight High-Strength Concrete
[0030] Performance detection test: Compressive strength tests were carried out on the concrete specimens prepared in each example. The concrete specimens were 15 cm×15 cm×15 cm cubes, three in each group. After molding, they were cured according to the standard method (temperature 20°C±2°C, relative humidity above 95%RH); the dry density was measured by the method of crushing specimens and drying. The obtained performance results are shown in Table 2.
[0031] Table 2 Test Data Table of Compressive Strength Performance and Dry Density
[0032] It can be concluded from the test data that lightweight high-strength concrete with a 28-day strength grade of LC50 or above was prepared by the method of the present invention, and its dry density is less than 1800 kg / m 3 , and there is a large strength surplus.
[0033] See Figure 4 and Figure 5 , which are the images of the concrete failure surfaces in Experimental Group 1 and Experimental Group 2 respectively, and there is no obvious concentration of aggregates.
[0034] The above examples are the preferred embodiments of the present invention, but the embodiments of the present invention are not limited by the above examples. The above examples only express several embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present invention, several deformations and improvements can still be made, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the invention patent should be subject to the appended claims.
Claims
1. A preparation method of a high-stability lightweight high-strength concrete, characterized in that, It includes the following steps: Step S1, pretreatment: Pre-wet fly ash ceramsite and shale ceramsite sand respectively until they reach the saturated surface dry state, and at the same time mix water and water reducer to form a chemical admixture solution; Step S2, grouting modification: Use a grouting pump to conduct pressure grouting treatment on the saturated surface dry fly ash ceramsite to obtain grouting-modified ceramsite. Among them, the mixing ratio of the grouting liquid used for the pressure grouting is: by mass, 450 - 550 parts of cement, 40 - 60 parts of silica fume, 5 - 7 parts of water reducer, and 100 - 160 parts of water; Step S3, density measurement: Place the fly ash ceramsite after pressure grouting modification in a ventilated and dry place to dry. After the surface is completely hardened, pour it into a concrete measuring cylinder; Measure the volume of the grouted and modified ceramsite by the drainage method, and through the formula ; Calculate the density of the modified ceramsite, where m0 is the mass of fly ash ceramsite, V is the volume of the volumetric cylinder, V 排 is the volume of the discharged clean water; Step S4, density balance adjustment: According to the formula ; Calculate the density of the mortar, and make ρ by adding 0 - 100 kg of cenospheres B =ρ T ; Step S5, staged mixing: In the first stage, dry-mix silica fume, cement, cenospheres, and ordinary sand for 2.0 - 3.0 min; in the second stage, add saturated surface dry shale ceramsite sand and chemical admixture solution and mix for 3 - 4 min; in the third stage, add modified ceramsite and mix for 3.0 - 5.0 min to prepare high-stability lightweight high-strength concrete.
2. The preparation method according to claim 1, wherein In the volume measurement by the drainage method, a 10L standard test cylinder is selected for the volume of the volumetric flask, and the filling height error is controlled within ±5 mm during measurement.
3. The preparation method according to claim 1, wherein The amount of cenospheres added is determined by the linear fitting formula ; Calculation, where a is the slope, b is the intercept; x is the mass of the cenospheres added, in kg, and ρ B is the mortar density, in kg / m 3 .
4. The preparation method according to claim 1, wherein The following mixing ratios are adopted for each component: 800 kg of fly ash ceramsite, 400 kg of shale ceramsite sand, 500 kg of cement, 50 kg of silica fume, 275 kg of ordinary sand, 6 kg of water reducer, 65 kg of water; the mixing ratio of the grouting liquid is 500 kg of cement, 50 kg of silica fume, 6 kg of water reducer, and 125 kg of water; density of saturated surface dry shale ceramsite sand: 1208 kg / m³; density of cement: 3100 kg / m³; density of silica fume: 900 kg / m³; density of ordinary sand: 2600 kg / m³; density of water reducer: 1100 kg / m³; density of water: 1000 kg / m³; density of cenospheres: 500 kg / m³; The linear equation obtained by fitting is ρ B = -2.7788x + 1778.8; Since ρ B = ρ T , ρ T is substituted into the linear equation to calculate the appropriate content of cenospheres.
5. A high-stability lightweight high-strength concrete, characterized in that, The mass ratio of each component of the concrete is (kg / m 3 ): 730 - 870 of grouting-modified fly ash ceramsite, 300 - 500 of saturated surface dry shale ceramsite sand, 450 - 550 of cement, 40 - 60 of silica fume, 260 - 290 of ordinary sand, 5 - 7 of water reducer, 0 - 100 of cenospheres, and 50 - 80 of water.